2008
DOI: 10.1044/0161-1461(2008/038)
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Evidence-Based Practice to Nonspeech Oral Motor Treatments

Abstract: Despite their use for many years and their popularity among some SLPs for the treatment of a wide variety of speech problems in children and adults, NSOMTs are controversial because sufficient evidence does not exist to support their effectiveness in improving speech. Moreover, limited evidence exists for the use of NSOMTs to facilitate nonspeech activities. Therefore, the available evidence does not support the continued use of NSOMTs as a standard treatment and they should be excluded from use as a mainstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 55 publications
(66 reference statements)
2
35
0
4
Order By: Relevance
“…Our findings indicated that only one fourth of the eligible nurses and AHPs responded to the survey, with a significantly higher response rate among AHPs. Despite this disappointing overall response rate, it is comparable with some studies examining EBP‐B and EBP‐I scores among nurses and other AHPs in acute care settings . An exception is the recent descriptive study in the Nordic country by Stokke et al which had a response rate above 50% .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our findings indicated that only one fourth of the eligible nurses and AHPs responded to the survey, with a significantly higher response rate among AHPs. Despite this disappointing overall response rate, it is comparable with some studies examining EBP‐B and EBP‐I scores among nurses and other AHPs in acute care settings . An exception is the recent descriptive study in the Nordic country by Stokke et al which had a response rate above 50% .…”
Section: Discussionsupporting
confidence: 65%
“…and EBP-I scores among nurses 25 and other AHPs in acute care settings. 8,26 An exception is the recent descriptive study in the Nordic country by Stokke et al which had a response rate above 50%. 27 The low response and high attrition rates may in themselves be revealing.…”
Section: Discussionmentioning
confidence: 99%
“…또한 이러 한 구강 운동 기능과 말 산출과의 관련성에 대해서는 선행 연 구마다 서로 다른 결과들을 보이고 있다 [22], [27]. [18], [21], [23]. [8], [9], [25].…”
Section: 말소리와 음성과학 제5권 제2호 (2013)unclassified
“…Indeed, there is an emerging literature that discusses evidence-based practice as it applies specifically to the treatment of speech sound disorders (e.g. Kamhi, 2006;Tyler, 2006;Lass and Pannbacker, 2008). To foster evidence-based thinking, Baker and McLeod (2004) have modelled an approach for extrapolating evidence from the literature and infusing evidence-based principles into clinical practice.…”
Section: Introductionmentioning
confidence: 98%